Leadership for integrated care: a case study. Issue 2 (4th February 2020) - Kozlowska, Olga; Seda Gombau, Gemma; Rea, Rustam
Abstract : Purpose: Integration of health services involves multiple interdependent leaders acting at several levels of their organisation and across organisations. This paper aims to explore the complexities of leadership in an integrated care project and aims to understand what leadership arrangements are needed to enable service transformation. Design/methodology/approach: This case study analysed system and organisational leadership in a project aiming to integrate primary and specialist care. To explore the former, the national policy documents and guidelines were reviewed. To explore the latter, the official documents from the transformation team meetings and interview data from 17 health-care professionals and commissioners were analysed using thematic analysis with the coding framework derived from the comprehensive and multilevel framework for change (Ferlie and Shortell, 2001). Findings: Although integration was supported in the narratives of the system and organisational leaders, there were multiple challenges: insufficient support by the system level leadership for the local leadership, insufficient organisational support for (clinical) leadership within the transformation team and insufficient leadership within the transformation team because of disruptions caused by personnel changes, roles ambiguity, conflicting priorities and insufficient resources. Practical implications: This study provides insights into the interdependencies of leadership across multiple levels and proposes steps to maximise the success of complex transformational projects. Originality/value: This study's practical findings are useful for those involved in the bottom-up integrated projects, especially the transformation teams' members. The case study highlights the need for a toolkit enabling local leaders to operate effectively within the system and organisational leadership contexts.